Advancing equity in breast cancer care: strategies to enhance mammography screening among women with disabilities in Saudi Arabia - Almohammed, Huda I.; Hamd, Zuhal Y.; Abuzaid, Mohamed M. (Frontiers in Oncology, 2025)
IntroductionBreast cancer is a significant public health issue worldwide, especially in Saudi Arabia, where it is the most prevalent cancer among women. Early detection through mammography is crucial, but disparities in screening accessibility for women with disabilities are evident. This study builds upon previous research to address these disparities. The study aims to develop and evaluate comprehensive educational and healthcare strategies to enhance mammography screening participation among Saudi women with disabilities. The study focuses on increasing screening rates and healthcare equity by addressing barriers and leveraging facilitators specific to this demographic.MethodsThis cross-sectional study was conducted across various regions in Saudi Arabia, targeting women with disabilities aged 40–69 years. Data collection involved a structured questionnaire, distributed both physically and online, focusing on demographic details, breast cancer screening practices, and barriers to access. The study also examined the effectiveness of various educational and healthcare interventions. Data analysis utilized IBM SPSS Statistics Version 26, employing chi-square tests and logistic regression.ResultsThe study’s demographic analysis revealed a diverse population with various disabilities and educational levels. Findings showed that 54.4% of participants found healthcare facilities only partially accessible, and 62.5% faced barriers in accessing breast cancer screening services. The majority (91.5%) had support systems or caregivers. Interventions focusing on educational campaigns, healthcare provider training, and improving facility accessibility were analyzed for their impact.ConclusionThe study underscores the necessity of inclusive healthcare practices and highlights the effectiveness of targeted interventions in improving mammography screening rates among women with disabilities. Collaborative efforts among healthcare providers, policymakers, and advocacy groups are crucial for addressing these disparities. Future research should focus on understanding specific challenges across diverse populations, assessing the long-term impact of improved screening rates, and evaluating the cost-effectiveness of interventions. This research contributes significantly to advancing healthcare equity in breast cancer screening for women with disabilities in Saudi Arabia.